Contributions to the study of gomphocerine grasshoppers calling songs (Orthoptera: Acrididae: Gomphocerinae) with notes on taxonomic status and distribution of some forms from Kyrgyzstan - Tishechkin, Dmitri Yu. (Zootaxa, 2017)
Male calling songs of 10 widely distributed species of Gomphocerinae from localities in Kyrgyzstan were investigated. In all species songs of males from the Central Asiatic and European populations are almost identical in spite of the fact, that in some species localities in Kyrgyzstan are isolated from the main parts of their ranges by the deserts of the South Kazakhstan and Central Asia. Glyptobothrus maritimus is the only species from G. biguttulus group widely distributed over all the territory of Kyrgyzstan. G. mollis was found only in the North and Central Tien Shan Mts.; no other species of this group were found in Kyrgyzstan. Chorthippus apricarius from the Central and West Tien Shan Mts. does not differ from the nominotypical subspecies in the calling song pattern and demonstrates variability of diagnostic characters used earlier for distinguishing between Ch. apricarius apricarius and Ch. apricarius asiaticus. This gives grounds for establishing a synonymy Ch. apricarius apricarius (Linnaeus, 1758) = Ch. apricarius asiaticus Mistshenko, 1951, syn. n.